Effects of Vestibular Stimulation on Balance in Children with Quadriplegic Cerebral Palsy - Asma Bashir, Hira Arshad, Amber Shabbir, Farwa Abid, Muhammad Usman Khalid, Rehan Ramzan Khan, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of the study was to determine the effects of vestibular stimulation on balance in quadriplegic cerebral palsy. Methodology: This was quasi experimental study in which total 44 quadriplegic cerebral palsy children were included who have no associated neurogenic conditions which may be aggravated with vestibular stimulation such as epilepsy or other orthopedic or functional complication. The children were assessed by an independent assessor before and after 6 weeks of vestibular stimulation. The assessment was made on gross motor measure and pediatric evaluation disability index. The data was analyzed using SPSS 20.0. Paired sample t test was used for pre-post testing. Results: The descriptive statistics of paired samples regarding Gross Motor Function Measure showed mean and standard deviation to be 49.61±1.75 and 64.54±1.04 before and after treatment, respectively. Paired sample testing for pre-post treatment measurement of mean score of Gross Motor Function Measure (GMFM) showed that mean difference and standard deviation found to be 14.93±1.90 with a significant p value 0.00. The descriptive statistics of paired samples regarding Total PEDI score showed mean and standard deviation to be 42.88±0.86 and 51.47±1.24 before and after treatment, respectively. Paired sample testing for pre-post treatment measurement of mean score of total Pediatric Evaluation Disability Inventory (PEDI) showed that mean difference and standard deviation found to be 8.59±1.48 with a significant p value 0.00. Conclusion: The findings of study concluded that vestibular stimulation has significant effect of vestibular stimulation on balance in quadriplegic cerebral palsy. Moreover, there were seen significant improvement in other domains such as behavior, emotions, psychology and interactive learning approach. Keywords: Cerebral Palsy, Quadriplegia, Child, Vestibular Stimulation